Development of a PCR Assay to Detect Low Level Trypanosoma cruzi in Blood Specimens Collected with PAXgene Blood DNA Tubes for Clinical Trials Treating Chagas Disease. - Bo Wei; Lei Chen; Miho Kibukawa; John Kang; Hetty Waskin; Matthew Marton (Public Library of Science (PLoS), 2016)
Chagas disease is caused by the parasitic infection of Trypanosoma cruzi (T. cruzi). The STOP CHAGAS clinical trial was initiated in 2011 to evaluate posaconazole in treating Chagas disease, with treatment success defined as negative qualitative PCR results of detecting the parasites in blood specimens collected post-treatment. PAXgene Blood DNA tubes were utilized as a simple procedure to collect and process blood specimens. However, the PAXgene blood specimens challenged published T. cruzi PCR methods, resulting in poor sensitivity and reproducibility. To accurately evaluate the treatment efficacy of the clinical study, we developed and validated a robust PCR assay for detecting low level T. cruzi in PAXgene blood specimens. The assay combines a new DNA extraction method with a custom designed qPCR assay, resulting in limit of detection of 0.005 and 0.01 fg/μl for K98 and CL Brener, two representative strains of two of T. cruzi's discrete typing units. Reliable qPCR standard curves were established for both strains to measure parasite loads, with amplification efficiency ≥ 90% and the lower limit of linearity ≥ 0.05 fg/μl. The assay successfully analyzed the samples collected from the STOP CHAGAS study and may prove useful for future global clinical trials evaluating new therapies for asymptomatic chronic Chagas disease.